2013
DOI: 10.1007/s10815-013-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for DHEA supplementation in women with diminished ovarian reserve?

Abstract: Purpose Poor ovarian reserve and poor ovarian response presents a challenge to IVF centers. Dehydroepiandrosterone (DHEA) supplementation is increasingly being used by many IVF centers around the world in poor responders despite the lack of convincing data. We therefore examined the rationale for the use of DHEA in poor responders, address the relevant studies, present new data, and address its potential mechanisms of action. Methods All published articles on the role of DHEA in infertile women from 1990 to Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…43 Recently, short-term treatment with dehydroepiandrosterone, an adrenal steroid available as an oral supplement, has been suggested to offer some hope in improving the biology of any residual gametes in the ovaries of young women diagnosed with POI. [44][45][46] Despite the recognized reproductive compromise, women diagnosed with POI remain at risk for unplanned conception, given that spontaneous resumption of follicular activity is not uncommon. Contraceptive strategies are thus recommended for those wishing to avoid pregnancy.…”
Section: Reproductive Concernsmentioning
confidence: 99%
“…43 Recently, short-term treatment with dehydroepiandrosterone, an adrenal steroid available as an oral supplement, has been suggested to offer some hope in improving the biology of any residual gametes in the ovaries of young women diagnosed with POI. [44][45][46] Despite the recognized reproductive compromise, women diagnosed with POI remain at risk for unplanned conception, given that spontaneous resumption of follicular activity is not uncommon. Contraceptive strategies are thus recommended for those wishing to avoid pregnancy.…”
Section: Reproductive Concernsmentioning
confidence: 99%
“…The age of patients varied from 21 to 42 years. According to Fratharelli and Peterson's work [9], patients with testosterone levels less than 20 ng/dl on day 3 were five times less likely to achieve success in IVF treatment. Patients were divided into 2 groups.…”
Section: Study Populationmentioning
confidence: 99%
“…Yingying Qin's group suggested that basal T level was a predictor for ovarian response and pregnancy outcome in women with diminished ovarian reserve; but could not in those with normal serum FSH [8]. However, Fratharelli and Peterson's study showed that patients with Day 3 testosterone level lesser than 20 ng/dl were five time less likely to achieve pregnancy [9]. This might be explained by limited sample size and heterogeneous population mixed by patients with polycystic ovary syndrome (PCOS) and/or endometriosis as PCOS and endometriosis are associated with higher or lower serum T levels.…”
Section: Introductionmentioning
confidence: 99%
“…Following the early cancellation of the treatment cycle, administration of pretreatment adjuvants like dehydroepiandrosterone sulphate (DHEA), growth hormone, and/or testosterone, can reduce the number of cycles of the potentially poor responders without several failed IVF-ET treatment cycles [Eftekhar et al 2013;Fouany and Sharara 2013;Fusi et al 2013;Narkwichean et al 2013;Singh et al 2013;Yilmaz et al 2013]. In a randomized study Eftekhar et al [2013] evaluated the IVF-ET cycle outcome after the addition of growth hormone in an antagonist protocol among poor responders.…”
Section: Discussionmentioning
confidence: 99%